Pengendalian Mutu Lekker dengan Checksheet, Diagram Pareto, dan Fishbone pada Usaha Lekkerz Enakk Cabang Bogor - Bobi Setiawan; Zulhida Dewi; Yosiana Mangguh Pertisaian; Putra Bagaskhara Andi Unru; Ananda Ariesta Rifiani; Shiddiqa Hayasya Zhafira (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze quality control at the Lekkerz Enakk business in Bogor branch using three statistical tools, namely Checksheet, Pareto Diagram, and Fishbone. Data collection was conducted through interviews with the owner, admin, and employees, as well as direct observation at the nearest branch location regarding the production process. Based on the results of the observation, three defects were found that frequently occurred during the production process within a period of seven days with the most dominant lekker product damage being a non-crispy texture (42%), and non-uniform color (27%). Based on the fishbone analysis, these defects were caused by Man (human), Machine (machine) factors. The implications of this study indicate that it is necessary to improve operational standards, workforce training, and supervision of raw materials and production equipment to maintain the quality and efficiency of the lekker production process at the Lekkerz Enakk business in Bogor.